Ekonomiczna wartość dodana i strategiczna karta wyników jako koncepcje uzupełniające się w procesie kreowania wartości - Świerk, Joanna (Economic value added and balanced scorecard as complementary concepts in the process of value creation, 2006)
This paper discusess the possibility to combine the use of EVA measure with the use of Balanced Scorecard approach. It describes definitions of this tools, origin, advantages and disadvantages, and then considers one approach for using the two concepts together. EVA focuses exclusively on financial aspects while the Balanced Scorecard considers financial measures as just one of several important perspectives. The paper concludes that when EVA is used in conjunction with the Balanced Scorecard approach, it can be a powerful basis for encouraging organisational change and performance improvement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 400-409